Emergency care for palliative patients in the emergency room: A literature review - Ni Luh Putu Inca Buntari Agustini; Ni Luh Dwi Indrayani; I Nyoman Widiadnyana; Ni Luh Putu Yudi Aprianini; Putu Indah Jelita Lestari; Ni Ketut Erawati; I Made Jaya Kusuma; Vinda Ekabudiningsih (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: A lot of research has been done on the treatment of palliative patients who come to the emergency department. Although there are several models, it is still difficult to integrate palliative care into the ED. Purpose: To determine how emergency care for palliative patients is implemented in the emergency department. Method: The PCC framework (Population: palliative patients, Concept: emergency care, Context: emergency department) was used to generate the article questions for this literature review. A search for articles was conducted during November and December, 2024. Pubmed, the ScientDirect database and other resources were used as data sources. “Palliative care